Sahabat Ibu Balita" Program to Improve Mother's Knowledge and Skills in Monitoring The Growth of Infants Aged 0-6 Months - Miftakhur Rohmah (Health Notions, 2017)
The first 6 months of infant life is a golden opportunity for early detection, as well as a growth assessment. Special forms of growth and development are stimulation. Stimulation should be done routinely, continuously at every opportunity and in all infants and toddlers. Based on the fact that there are many mothers who do not know how to perform good stimulation and unskilled in stimulating the result is still found the existence of parents who do not provide stimulation of the baby with routine. The purpose of this study was to determine "differences in mother's knowledge and skills in monitoring of growth and development infants aged 0-6 months among mothers who applied “Sahabat Ibu Balita” and those who did not apply the “Sahabat Ibu Balita”. The design of this research was quasi-experiment with pre-posttest with control group. The samples used were parents who had babies aged 0-6 months in the work area of Babakansari Community Health Center. Sample sizw was 66, then divided into 2 groups that was intervention group and control group. They were selected by multistage sampling and executed in December 2016 to January 2017. Result of research by Chi square test there was a significant difference of intervention group and control group on the knowledge and skills. The application of “Sahabat Ibu Balita” as a strategy to support the use of “KIA book” for mother's knowledge and skill in monitoring the growth and development was more optimal. Keywords: Infant, Growth, Knowledge, Skills, “Sahabat Ibu Balita” program